2020
DOI: 10.3390/toxins12070461
|View full text |Cite
|
Sign up to set email alerts
|

Mycotoxins and the Enteric Nervous System

Abstract: Mycotoxins are secondary metabolites produced by various fungal species. They are commonly found in a wide range of agricultural products. Mycotoxins contained in food enter living organisms and may have harmful effects on many internal organs and systems. The gastrointestinal tract, which first comes into contact with mycotoxins present in food, is particularly vulnerable to the harmful effects of these toxins. One of the lesser-known aspects of the impact of mycotoxins on the gastrointestinal tract is the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0
4

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 253 publications
(261 reference statements)
3
17
0
4
Order By: Relevance
“…In conclusion, our data confirmed the hypothesis of Gonkowski et al [25] about a potential alteration of ENS by at least some food-associated mycotoxins. Our data generated using rat EGCs in vitro confirmed the pioneer work of Rissato et al [32] that showed that deoxynivalenol is able to affect proliferation and viability of EGCs in vivo in rats.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In conclusion, our data confirmed the hypothesis of Gonkowski et al [25] about a potential alteration of ENS by at least some food-associated mycotoxins. Our data generated using rat EGCs in vitro confirmed the pioneer work of Rissato et al [32] that showed that deoxynivalenol is able to affect proliferation and viability of EGCs in vivo in rats.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, although less data are available compared to IECs, the impact of mycotoxins on viability and functions of brain cells has been evaluated and described (for review [12,[15][16][17][18][19][20][21]). Although the enteric nerve system (ENS) similarly to IECs may be exposed to high doses of mycotoxins, surprisingly only few studies have investigated the impact of those toxins on cells of this system ( [22][23][24] and for review [25]). Even less is known about the impact of mycotoxins on enteric glial cells (EGCs).…”
Section: Introductionmentioning
confidence: 99%
“…The ENS, characterized by complex anatomy, a considerable neurochemical diversity and autonomy against the central nervous system, is situated in the wall of the esophagus, stomach and intestines [ 14 , 15 ]. Its organization depends on the species [ 16 , 17 ]. In the intestines of domestic pigs, the ENS is composed of three kinds of plexuses [ 16 , 18 , 19 , 20 ]: (1) the myenteric plexus (MP) in the intestinal muscular layer, (2) the outer submucous plexus (OSP) in the submucosal layer in the vicinity of the muscular layer and (3) the inner submucous plexus (ISP), also in the submucosal layer but close to the mucosal layer ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies investigating DON effects on organisms have reported histopathological changes of the gastrointestinal tract such as inflammatory infiltration, necrotic changes in the intestinal villi, edema of lamina propria, a decrease in the number of goblet cells in the jejunum and the ileum, intensification of apoptosis and degeneration of lymphoid cells in the gastrointestinal tract [ 67 , 68 ]. Considering the findings of inflammation of the intestinal mucosa with the presence of eosinophils, it should be stated that a non-specific inflammatory reaction did occur, probably arising as a result of an exaggerated reaction of the immune system.…”
Section: Discussionmentioning
confidence: 99%